The Religious Fatwa between Contemporary Developments and the Pressures of the Cultural Unconscious (The International Journal of Educational Sciences and Arts, 2025)
This study aims to examine the religious fatwa as a dynamic legal instrument that interacts with contemporary transformations, focusing on the influence of cultural unconsciousness in shaping attitudes and perspectives within Muslim societies. The research problem lies in the fact that many fatwas are unconsciously affected by cultural and social factors, which leads to rigidity in legal rulings and limits their ability to respond to modern developments.The significance of this study emerges from highlighting the relationship between the religious text and the demands of the modern world, and from seeking to develop mechanisms of fatwa issuance that preserve the objectives of Sharia while balancing religious stability with social change.The research adopts the descriptive method to analyze selected fatwas and trace their evolution, alongside the cultural criticism approach to understand how cultural and social pressures influence the formulation of religious discourse.The study concludes that developing the fatwa requires profound religious and cultural awareness, as well as continuous institutional efforts to ensure that fatwas remain consistent with the higher objectives of Sharia without being subject to the unconscious pressures of culture or changing realities.
Keywords: Religious Fatwa; Contemporary Developments; Cultural Unconsciousness; Ijtihad; Awareness